Yeast of the genus Malassezia. New data - Zawirska, Agnieszka (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2004)
It seems that genus Malassezia might play a certain role in pathogenesis of various skin diseases. So far, the association between the yeast and pityriasis versicolor was most often described in literature. In the paper the data about the structure, biochemistry and physiology of Malassezia genus were collected. The history of the study of the fungi was also presented. Recent molecular methods led to taxonomic reclassification of genus Malassezia and final definition of seven species. In the article we focused on typical cutaneous diseases caused by the yeast, but also more and more often reported systemic ones.